Уроки изобразительного искусства в среднем звене школы для детей с тяжелыми нарушениями речи - Рибцун, Ю. В.
The article highlights the current issues of organizing and conducting classes in the visual arts in 6-7 classes of educational institutions for children with severe speech disorders. Particular emphasis is placed on the disclosure features psycho-verbal activities of student’s mid-level school, which is developed taking into, account the author’s program in fine arts, as well as a list of benchmarks three components formation of industry competence pupils at the end of the school year.
Keywords: Изобразительное искусство